2017
DOI: 10.3233/jhd-170264
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Understanding of Energy Impairment in Huntington’s Disease Brain

Abstract: This review systematically examines the evidence for shifts in flux through energy generating biochemical pathways in Huntington’s disease (HD) brains from humans and model systems. Compromise of the electron transport chain (ETC) appears not to be the primary or earliest metabolic change in HD pathogenesis. Rather, compromise of glucose uptake facilitates glucose flux through glycolysis and may possibly decrease flux through the pentose phosphate pathway (PPP), limiting subsequent NADPH and GSH production nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 251 publications
(374 reference statements)
2
38
0
Order By: Relevance
“…Like the Q175 mutants, the R6/2 mice also exhibited episodes of hypothermia, particularly evident in the dark period. Overall, there is strong evidence for mitochondrial dysfunction in HD as well as in other neurodegenerative diseases (Carmo, Naia, Lopes, & Rego, ; Dubinsky, ; Franco‐Iborra, Vila, & Perier, ; Kuhl et al, ; Naseri et al, ). Unintended weight loss is a hallmark of HD patients and a recent study found that a high body mass index (BMI) is associated with a significantly slower rate of functional, motor, and cognitive deterioration (van der Burg et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Like the Q175 mutants, the R6/2 mice also exhibited episodes of hypothermia, particularly evident in the dark period. Overall, there is strong evidence for mitochondrial dysfunction in HD as well as in other neurodegenerative diseases (Carmo, Naia, Lopes, & Rego, ; Dubinsky, ; Franco‐Iborra, Vila, & Perier, ; Kuhl et al, ; Naseri et al, ). Unintended weight loss is a hallmark of HD patients and a recent study found that a high body mass index (BMI) is associated with a significantly slower rate of functional, motor, and cognitive deterioration (van der Burg et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Glu can also be implicated in energy production through its equilibrium with alpha‐ketoglutarate, an intermediate of the Krebs cycle. One can hypothesize that dynamic adaptations of metabolic fluxes may take place during the animal's lifespan in order to counterbalance disturbance of homeostasis and energy production due to mutant huntingtin 39 . One can assume that such compensatory mechanisms would be more efficient in slowly progressive models than in severe forms, where the aggravations of alterations of brain cells are probably faster and might not be counterbalanced.…”
Section: Discussionmentioning
confidence: 99%
“…For example, HD patients show excessive weight loss despite normal food intake [165]. Glucose metabolism is decreased in affected brain regions of HD patients, and post-mortem brain samples exhibit decreased mitochondrial respiratory complex activity [166,167]. Moreover, mitochondrial malfunction occurs not only in affected brain regions but also in peripheral tissues such as skin fibroblasts derived from HD patients [168].…”
Section: Ptms Associated With Mitochondrial Abnormalities and Defectsmentioning
confidence: 99%